2014
DOI: 10.1590/1677-3225v13n2a14
|View full text |Cite
|
Sign up to set email alerts
|

Electromyographic evaluation of the effect of ultrasound with muscle stretching in temporomandibular disorder: a clinical trial

Abstract: Aim: To investigate the electromyographic activity of masticatory muscles in women with myogenic or mixed TMD treated with ultrasound and ultrasound associated with stretching. Methods: Sixteen women with myogenic or mixed TMD, according to the Research Diagnostic Criteria for Temporomandibular Disorder (RDC/TMD), participated in the study. The patients were evaluated using surface electromyography (sEMG) of the masseter and anterior temporalis muscles, during maximum intercuspation, before and immediately aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 17 publications
1
1
1
Order By: Relevance
“…(17) Alterations in the electrical activity of masticatory muscles in patients with TMD has been related to muscle pain, emotional factors, stress and tension, moreover, greater muscle asymmetry can be observed in this group of patients during the sitting evaluation and MI. (18,19) As the results of this study, authors demonstrated in their study a greater activity of the left anterior temporal than the masseter in patients with TMD, when evaluated during MI. (20) The inversion in the pattern of electrical activity in masticatory muscles can also be attributed to possible postural action performed by the anterior temporal muscle and the relation between greater contact of the anterior teeth and relative increase in the activity of this muscle.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…(17) Alterations in the electrical activity of masticatory muscles in patients with TMD has been related to muscle pain, emotional factors, stress and tension, moreover, greater muscle asymmetry can be observed in this group of patients during the sitting evaluation and MI. (18,19) As the results of this study, authors demonstrated in their study a greater activity of the left anterior temporal than the masseter in patients with TMD, when evaluated during MI. (20) The inversion in the pattern of electrical activity in masticatory muscles can also be attributed to possible postural action performed by the anterior temporal muscle and the relation between greater contact of the anterior teeth and relative increase in the activity of this muscle.…”
Section: Discussionsupporting
confidence: 56%
“…Similar values of muscle activity were found in women with TMD and mean age 25.69 ± 5.13. (18) Another study found higher values when compared to the results of this research (R MA = 1.71; L MA = 2.35; R AT = 2.55; L AT = 2.47). (2) The authors found that patients with different degrees of severity of TMD evaluated with electromyography in resting showed higher electrical activity of the masseter and temporal muscles, especially when such impairment is considered severe.…”
Section: Discussioncontrasting
confidence: 55%
“…When both sides contract in perfect symmetry and amplitude curves completely overlap, the POC value is 100% (Boufleur et al, 2014;Ferrario et al, 2000;Ries et al, 2008).…”
Section: Methodsmentioning
confidence: 99%